Overexpression of RsMYB1 Enhances Anthocyanin Accumulation and Heavy Metal Stress Tolerance in Transgenic Petunia - Ai, Trinh Ngoc; Naing, Aung Htay; Yun, Byung-Wook; Lim, Sun Hyung; Kim, Chang Kil (Frontiers in Plant Science, 2018)
The RsMYB1 transcription factor (TF) controls the regulation of anthocyanin in radish (Raphanus sativus), and its overexpression in tobacco and petunia strongly enhances anthocyanin production. However, there are no data on whether RsMYB1 is involved in the mechanisms underlying abiotic stress tolerance, despite strong sequence similarity with other MYBs that confer tolerance to different abiotic stresses. This study used an anthocyanin-enriched transgenic petunia line, PM6, expressing RsMYB1. The tolerance of the PM6 line to heavy metal stress was investigated by examining several physiological and biochemical factors, and the transcript levels of the genes related to metal detoxification and antioxidant activity were investigated. Under normal conditions (control conditions), transgenic petunia plants (T2-PM6) expressing RsMYB1, as well as wild-type (WT) plants, were able to thrive by producing well-developed broad leaves and regular roots. In contrast, a reduction in plant growth was observed when they were exposed to heavy metals (CuSO4, ZnSO4, MnSO4, and K2Cr2O7). However, T2-PM6 plants were found to be more tolerant to the stresses than the WT plants by showing superior results in all analyzed parameters. In addition, RsMYB1 overexpression enhanced the expression of genes related to metal detoxification (GSH and PCS) and antioxidant activity (SOD, CAT, and POX). These results suggest that enhanced expression levels of these genes would detoxify metal-induced stress and improve antioxidant activity, which are the main components of the mechanism underlying abiotic stress tolerance in petunia. Our findings demonstrate that RsMYB1 has potential as a dual-function gene that will improve anthocyanin production and heavy metal stress tolerance in horticultural crops.